2022
DOI: 10.7759/cureus.23040
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Inflammatory Orbitopathy Hiding Orbital Lymphoma

Abstract: The incidence of lymphoma is constantly increasing worldwide. The reasons for this increase are unclear and likely multiple. B cell lymphomas represent the majority of non-Hodgkin lymphomas. Primary orbital localization remains a rare entity to think about in order to avoid missing a therapeutic emergency. In this article, we report the case of a 52-year-old man who has been treated for five years for an inflammatory orbitopathy with steroids, but the worsening of the clinical condition and the installation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…According to a report, the median latency between the diagnosis of thyroid orbitopathy and the development of periocular lymphoma in patients was 17.5 years [13]. According to another case report, the time to diagnosis was five years [14]. Our patient was diagnosed with lymphoma within two years of the diagnosis of euthyroid ophthalmopathy.…”
Section: Discussionmentioning
confidence: 55%
“…According to a report, the median latency between the diagnosis of thyroid orbitopathy and the development of periocular lymphoma in patients was 17.5 years [13]. According to another case report, the time to diagnosis was five years [14]. Our patient was diagnosed with lymphoma within two years of the diagnosis of euthyroid ophthalmopathy.…”
Section: Discussionmentioning
confidence: 55%
“…The incidence of primary orbital lymphoma has increased in recent years; however, the causes of this disease remain unclear. Several investigators suggested that the development of lymphoma, especially EMZL, may be associated with longterm chronic infections of the patients, such as chlamydia infection, helicobacter pylori infection, and chronic hepatitis [25][26][27][28] . The immune status was also considered to be associated with the development of orbital lymphoma [29][30] .…”
Section: Orbital Lymphoma Clinical Characteristicsmentioning
confidence: 99%